INOVASI PROGRAM WIRAUSAHA PEMUDA KABUPATEN TEGAL PADA DINAS KEPEMUDAAN, OLAHRAGA, DAN PARIWISATA KABUPATEN TEGAL - Athalla Nurfitri, Khaerisma; Hayu Dwimawanti, Ida; Puspo Priyadi, Budi (Journal of Public Policy and Management Review, 2024)
The Tegal Regency Youth Entrepreneurship Program (WP) as a regional innovation of Tegal Regency has succeeded in developing budding youth entrepreneurs every year since 2019 and has indirectly contributed to reducing youth unemployment and can open up new job opportunities. Apart from that, the central and other regional governments are using the Tegal Regency WP Program innovation as an example for creating national policies and programs related to youth entrepreneurship. The aim of this research is to analyze more deeply why the Tegal Regency WP Program was successful and to analyze the factors supporting the success of the WP Program innovation. The method used is descriptive qualitative research with data collection using interview and documentation techniques. The results of the study indicate that the WP Program innovation in Tegal Regency can be successful because of good institutions, such as clear and complete regulations, program implementers comply with applicable rules and serve program participants well. Furthermore, because Disporapar and external actors of the program have a good relationship. In addition, the community is very enthusiastic about participating as program participants and is also included in the collaborative work team. The supporting factors for the success of this innovation are the good leadership of the regional head and the head of Disporapar Tegal Regency, good team and budget management, risk management, competent human resources, and the use of technology such as websites and social media. So, the success of the innovation of the Tegal Regency WP Program was due to the good governance of innovation carried out by the Porapar Service as the person responsible for the program. It is hoped that the WP Program innovation will continue to be implemented sustainably in the next leadership period.